Fair principles for sustainable development : essays on environmental policy and developing countries / edited by Edward Dommen. - Dommen, Edward. (New horizons in environmental economics., 1993)
With the increasingly evident and widespread impact of economic activity on the environment, there is a growing concern in all parts of the world that environmental considerations should be more fully reflected in economic decision-making. The Polluter-Pays, User-Pays, and Precautionary principles are increasingly being used as guidelines for environmental policy, and yet their developmental implications have barely been explored.